Methods of Teaching English to Preschool Children and Methods of Learning English for Children (Eurasian Scientific Herald, 2022)
In this article, great importance is given to modern methods of teaching foreign languages in the process of preschool education in the Republic of Uzbekistan, as well as the effect of continuous education, which includes several technologies and modern teaching methods necessary for learning them. ways to increase the effectiveness of lessons by making them interested in learning foreign languages through games are described